Diseminasi Platform Online Shop berbasis Website dan Situs Belanja Online - Melinda, Melinda; Away, Yuwaldi; Yunidar, Yunidar; Raihan, Siti; Nazilla, Izza; Hasan, Vania Pratama (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This service was created with the aim of training partners who have businesses to develop their businesses by creating websites. Where the Website is one of the promotional media which is quite influential in this increasingly sophisticated technological era compared to other promotional media which still use paper such as brochures, posters and others. Websites are the cheapest, most effective and efficient promotional media if they can be managed properly. From any point of view, promotional media using websites still has more advantages, both from the point of view of distributing information, speed of information delivery, and even the price. The idea is to use pantheon.io as a hosting creation page and use several plugins to support website creation, both design and uploading product photos. The partners involved in this activity are online entrepreneurs engaged in selling fragrance products (perfume). The method we use in creating websites is the RAD (Rapid Application Development) method. As a result of this training and mentoring, partners will be able to take advantage of the use of websites and online shopping sites, so that the websites created can be useful for partners who have businesses to increase the target market for their products even wider.